ASSESS THE ADJUSTMENT PROBLEMS EXPERIENCED BY THE NEW ENTRANTS OF HEALTH PROFESSIONAL COURSES - Ms. Priyanka S. Meshram, Mrs. Jaya Gawai (International Journal of Modern Agriculture, 2020)
Background: The students’ change habits differ with their level of intelligence. Students at the college also have transition issues at school. You have parental problems, siblings because of shyness, aggressiveness. Because of new academic pattern, atmosphere and faculties they have academic adjustment problem. Learning inspiration, taking steps to meet academic demands and academic frustration are components of academic transition. Objectives: 1.To identify the adjustment problems experienced by the new entrants of professional courses. 2. To associate the adjustment problems, with their demographic variables of new entrants of professional courses. Material and method: An Descriptive research design study was undertaken to assess the adjustment problems experienced by the new entrants of health professional courses. Selected Colleges of health professional courses. In this study a total number of 120 students who fulfill the inclusion criteria were selected. Adjustment scale was developed for assess the adjustment level. Expected Results: This study is planned to assess the adjustment problems experienced by the new entrants of health professional courses. Hence, it is expected to identify the adjustment problems and may prevent them from counselling and anxiety may prevent them from bonding with their teachers and classmates. The conclusion will be drawn from the results and will be published in per review journal.